P4HA1 Regulates CD31 via COL6A1 in the Transition of Glioblastoma Stem-Like Cells to Tumor Endothelioid Cells - Han, Xiangming; Wang, Qiyan; Fang, Sheng; Wang, Jialin; Liu, Fusheng; Zhang, Junwen; Jin, Guishan (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is a common intracranial malignancy characterized by abundant and aberrant vasculature. The efficiency of existing antivascular treatments remains unsatisfactory. The transition of glioblastoma stem-like cells (GSCs) into tumor endothelioid cells (ECs) has been thought to cause glioma neovascularization and anti-angiogenesis tolerance, but the mechanisms regulating glioma transdifferentiation remains unclear. Our previous study found that P4HA1 regulates GSCs vascular mimicry in a hypoxic microenvironment, but the detailed molecular mechanism has not been determined. In this study, candidate protein COL6A1 was screened by mass spectrometry. In vitro experiments show that P4HA1 regulates the expression of CD31 via COL6A1, with the levels of expression of P4HA1, COL6A1 and the vascular endothelial molecular markers CD31 showing positive correlations in vivo assay. Altering the expression of P4HA1 in GSCs altered the expression of COL6A1 and CD31, thereby inducing glioma angiogenesis. In conclusion, this study revealed that the P4HA1/COL6A1 axis modulates the transdifferentiation process of GSCs into ECs. Interrupting this signaling axis can inhibit glioma angiogenesis, suggesting that this axis may be a novel target for antivascular therapy in patients with glioma.